The inhibitory effects of Gelam honey and its extracts on nitric oxide and prostaglandin E2 in inflammatory tissues - Kassim, Mustafa; Achoui, Mouna; Mansor, Marzida; Yusoff, Kamaruddin Mohd (Elsevier, 2010)
We investigated the effects of honey and its methanol and ethyl acetate extracts on inflammation in animal models. Rats’ paws were induced with carrageenan in the non-immune inflammatory and nociceptive model, and lipopolysaccharide (LPS) in the immune inflammatory model. Honey and its extracts were able to inhibit edema and pain in inflammatory tissues as well as showing potent inhibitory activities against NO and PGE2 in both models. The decrease in edema and pain correlates with the inhibition of NO and PGE2. Phenolic compounds have been implicated in the inhibitory activities. Honey is potentially useful in the treatment of inflammatory conditions.